Malin Kundang Folk Stories: Integration of Local Culture in Learning Narrative Texts - Berlian Ocsis; Tedi Permadi; Sumiyadi Sumiyadi; Yoga Prima; Bafirman Bafirman; Fiky Zarya (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to explore the role of the Malin Kundang folklore in the integration of local culture in the learning of narrative texts in schools. The background to this research is the need to integrate local culture in education, considering that Indonesia is rich in cultural heritage which can be used as a relevant learning source. The Malin Kundang folklore, as part of Minangkabau culture, contains moral values that can be internalized by students, such as respect for parents and awareness of the consequences of actions. The method used in this research is literature study, which examines various sources related to folklore, the values contained therein, and their application in the learning context. Through this analysis, it was found that folklore not only functions as a medium of entertainment, but also as an effective educational tool for improving students' literacy skills, especially in narrative writing. The results of this research show that the integration of local culture through Malin Kundang stories can enrich students' learning experiences, shape their character, and increase their love of culture. Apart from that, this story provides space for discussion about social values that are relevant to everyday life. Thus, the application of folklore in narrative text learning has great potential to strengthen students' cultural identity and support the preservation of Indonesia's cultural heritage.